Migration without Velocity Model in Curvelet Domain - Bona, Andrej; AlMaghlouth, Mohammed (EAGE, 2010)
We present a formulation of velocity-less time migration in curvelet domain. In particular, we first decompose pre-stack gathers to curvelets, which unlike wavelets also contain directional information. Then, we use this directional information to perform migration that does not require any velocity model. This migration is performed directly with the curvelet coefficients. The resulting image is reconstructed by applying the inverse curvelet transform. The process is illustrated on synthetic data and compared to Kirchhoff migration.